Growth and hydrogen production by three Chlamydomonas strains cultivated in a commercial fertilizer - Silva, Ana (2019)
In the present investigation, we report the growth and hydrogen production of two wild type Chlamydomonas reinhardtii strains isolated from a tropical oxidation pond in Costa Rica. The performance of these two new isolates was compared to that of Chlamydomonas reinhardtii CC124. All the strains were grown both in conventional Tris-Acetate-Phosphate medium (TAP) and in a commercial fertilizer medium (NPK 20-20-20). The growth of the new two isolates in medium formulated with fertilizer was higher than that attained with the reference strain (CC124). However, the hydrogen production performance of the strain CC124 in TAP-S and fertilizer were comparable, while the two new strains performed better in fertilizer, although the total hydrogen production was lower than that achieved with CC124. By using fertilizer it is possible to reduce the cost of chemical reagents by about 63% compared to TAP. Another advantage of the fertilizer is that it does not contain sulfur, therefore it can be directly used for hydrogen production using the Melis protocol.